Design of high frequency transformers in different shape of core using matlab program - Reem Falah Hassan; Kassim Rasheed Hameed (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper deals with the design, simulation and implementation of the high-frequency transformer for a push-pull converter. It also includes transformer design and simulation for two switches, two outputs forward converter. Design these transformers by building a program, this program is designed in MATLAB software using a graphical user interface (GUI). The program is aimed to reduce the efforts and reduce the time compare with the manual design which takes time and effort. This paper provided the shape and geometry of the core that can influence the efficiency of the converter by designing these transformers in two types of core. The design results were validated by simulation in power simulation software (PSIM), and compare the results of simulation and design.